2011
DOI: 10.1155/2011/561862
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Cigarette Smoke-Induced Proliferation of Lung Cells and Prevention by Vitamin C

Abstract: Lung cancer is the leading cause of cancer dearth. Cigarette smoking is the strongest risk factor for developing lung cancer, which is conceivably initiated by proliferation. Here, we show that low concentration of aqueous extract of cigarette smoke (AECS) causes excessive proliferation of human lung epithelial cells (A549) without any apoptotic cell death. The causative factor responsible for AECS-induced proliferation has been identified as p-benzoquinone (p-BQ). Coimmunoprecipitation and immunoblot experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Previous reports from our laboratory had indicated that p-BQ derived from cigarette smoke binds to the extracellular domain of EGFR in cultured human lung cells and activates EGFR constitutively [16] . Here, we showed binding of p-BQ with EGFR in the renal pelvis of vitamin C-restricted guinea pigs those developed CIS.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous reports from our laboratory had indicated that p-BQ derived from cigarette smoke binds to the extracellular domain of EGFR in cultured human lung cells and activates EGFR constitutively [16] . Here, we showed binding of p-BQ with EGFR in the renal pelvis of vitamin C-restricted guinea pigs those developed CIS.…”
Section: Resultsmentioning
confidence: 93%
“…Previously we had shown that p-BQ derived from CS activated EGFR and acted like a mitogen in cultured human lung cells [16] . Here, we showed that p-BQ activated EGFR in the renal pelvis apparently by binding to cysteine or lysine residues of the extracellular domain and induced aberrant phosphorylation of cytoplasmic tyrosine residuesinsert reference [17] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A number studies have shown that vitamin C inhibits proliferation of lung cancer cells, and demonstrates synergism with tea polyphenols by modulating different signaling pathways. [32][33][34][35] Studies have also shown that combination of ascorbic acid and α-tocopherol prevented smoke-induced lung squamous metaplasia in ferrets, 36 and a combination of vitamin C and vitamin K3 inhibited tumor growth and metastasis of Lewis lung carcinoma xenograft in mice. 37 In the 1970s, Linus Pauling promoted the use of vitamin C to prevent the common cold, and later for the treatment of cancer including lung cancer.…”
Section: Vitamin Cmentioning
confidence: 98%